PROSES METAKOGNISI SISWA DALAM PEMECAHAN MASALAH ALJABAR BERDASARKAN TAKSONOMI SOLO - Wasti Tampi; Subanji Subanji; Sisworo Sisworo (Graduate School of Universitas Negeri Malang, 2016)
This study describes the metacognition process of students in problem solving of algebra based on the SOLO taxonomy. This study used a qualitative approach with descriptive research. The results of this study suggest that the metacognition process of students that occurs in problems solving of algebra at the levels of unistructural, multistructural, relational and extended abstract includes the process: metacognitive awareness, metacognitive evaluating, and metacognitive regulating.Penelitian ini mendeskripsikan proses metakognisi siswa dalam pemecahan masalah aljabar berdasarkan taksonomi SOLO. Penelitian ini menggunakan pendekatan kualitatif dengan jenis penelitian deskriptif. Hasil penelitian menunjukkan bahwa proses metakognisi siswa yang terjadi dalam pemecahan masalah terkait dengan aljabar pada level unistruktural, multistruktural, relasional, dan extended abstract mencakup proses metacognitive awareness, metacognitive evaluating, dan metacognitive regulating.